Kontekstualisasi Surah al-Nūr Ayat 11-20 Pada Open Journal System Indonesia Kontemporer - Itrayuni, Itrayuni; Ashadi, Andri; Faizin, Faizin (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Several authors of journal articles discuss Surah al-Nūr verses 11-20 related to the ifki hadith. The author considers that some of these articles are strongly influenced by Abdullah Saeed's theory because there are aspects of the Qur'an's linguistic and historical context, both micro and macro, as well as contemporary contexts. In this theory there is the story of 'Aisyah r.a. that was slandered at the time of the Prophet known as the ifki hadith which was later enshrined in Surah al-Nūr verses 11-20. The purpose of this study is to elaborate on the extent to which the authors of the article contextualize surah al-Nūr verses 11-20. The method used in this research is a qualitative method with library research. The theory used in this study is Abdullah Saeed's theory with a contextual approach. The findings of this study are that in general, the articles that study Surah al-Nūr verses 11-20 have fulfilled the theory put forward by Abdullah Saeed. One of the articles that fulfill Abdullah Saeed's contextual interpretation is the article written by 'Ayun Masfufah that this article takes the past context and then relates it to the current context.